Assesing The Efficiency Of Central Java’s Regional Budget Realization Using Data Envelopment Analysis - Mario Rosario Wisnu Aji; Elisa Letizia (Equity: Jurnal Ekonomi, 2025)
This study evaluates the efficiency of Central Java’s 2022 Regional Budget (APBD) realization using a Variable Returns to Scale (VRS) input-oriented Data Envelopment Analysis (DEA) model. The study analyzes 35 regencies and cities using data from the Central Java Regional Budget Realization Report and Statistics Indonesia (BPS). Inputs include regional expenditure, employee expenditure, goods and services expenditure, capital expenditure, and other expenditures, while outputs consist of Gross Regional Domestic Product (GRDP) and the Human Development Index (HDI). Findings reveal that only 7 out of 35 regions (20%) achieved efficiency due to effective planning, streamlined budget processes, and robust supervision. Meanwhile, 28 regions (80%) exhibited inefficiencies linked to policy inconsistencies, limited planning capacity, and socio-economic constraints. For instance, some regions allocated substantial capital expenditure but failed to utilize funds effectively due to delayed infrastructure projects. These inefficiencies highlight the need for improved coordination, strategic planning, and stronger institutional capacity. Local governments and policymakers should ensure budget allocations align with regional priorities and improve financial management and transparency. Additionally, academics can contribute by providing research-based insights to support policy reforms. Strengthening these aspects will enhance public financial management, promoting sustainable economic growth and human development.